Are We Practicing What We Are Preaching? An Evaluation of Self-Determination Instructional Components in IEPs at a Midwestern High School - Lopez, Nancy; Stoner, Julia B. (Journal of the American Academy of Special Education Professionals, 2017)
Promoting self-determination in students with disabilities is recognized as an integral component of education today. For most students with disabilities, self-determination should be addressed through instruction and in the Individualized Education Program (IEP). Yet, IEPs are rarely evaluated to determine if goals targeting self-determination are present. This report focuses on one such evaluation. Specifically, an evaluation was conducted to assess whether the IEP goals for 286 high school students with disabilities attending a suburban high school in the Midwest included components of self-determination. The purpose of this report is to describe the evaluation process, identify the outcomes of the evaluation, and provide a discussion of the results in relation to current research. Limitations and implications for practice are presented.